2020
DOI: 10.3390/cancers12061417
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi Anemia Pathway Activation by FOXM1 is Critical to Bladder Cancer Recurrence and Anticancer Drug Resistance

Abstract: Although the 5-year survival rate of patients diagnosed with nonmuscle invasive bladder cancer (NMIBC) has reached 85%, more than 50% of patients suffer from frequent recurrences. To identify molecular targets associated with recurrence of NMIBC, we analyzed gene expression data and found that FOXM1 and FANCD2 were involved in recurrence. Therefore, we investigated how these genes were involved in the mechanism of recurrence and confirmed their usefulness as biomarkers. Investigation have shown that FOXM1 dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
(50 reference statements)
0
25
0
Order By: Relevance
“…NMIBC is clinically heterogeneous [ 5 ]. Despite considerable effort [ 7 , 8 , 9 , 10 , 11 ], the clinical heterogeneity of NMIBC means that there is a great need to identify subtypes with biological and clinical relevance. Here, we used data from multiple NMIBC patient cohorts to carry out transcriptome profiling analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…NMIBC is clinically heterogeneous [ 5 ]. Despite considerable effort [ 7 , 8 , 9 , 10 , 11 ], the clinical heterogeneity of NMIBC means that there is a great need to identify subtypes with biological and clinical relevance. Here, we used data from multiple NMIBC patient cohorts to carry out transcriptome profiling analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable effort has been devoted to uncovering the molecular characteristics and establishing prognostic models of NMIBC [ 7 , 8 , 9 , 10 , 11 , 19 ]. Recent transcriptomic profiling investigations revealed several distinct molecular subtypes relevant to tumor heterogeneity [ 7 ] and responsiveness of BCG therapy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang et al [12] reported that in bladder carcinoma cells, downregulation of FOXM1 suppress cell migration and invasion. Roh et al [13] reported that FOXM1 can be used as a useful tumor marker that are associated with anticancer drug resistance properties in NMIBC patients. Chen et al [14] con rmed upregulation of FOXM1 was related to bad progression free survival of NMIBC patients.…”
Section: Discussionmentioning
confidence: 99%